Guarantee optimization in energy performance contracting with real option analysis - Guo, Kai (2022)
Energy performance contracting has been regarded as an effective mechanism and adopted worldwide to improve energy efficiency and to lessen the increasingly worsen energy problem. Despite the beneficial intention of Energy performance contracting, it has not developed well as it should be. One of the fundamental reasons dragging down the rapid development is that Energy performance contracting may involve different stakeholders but the risk and profit allocation mechanism between them is complex, and the existing Energy performance contracting schemes are difficult to be simultaneously feasible and lucrative to different stakeholders. This research reviews the guarantee-saving scheme, one of the major schemes in Energy performance contracting projects, and discusses obstacles hindering its wide application: inadequate consideration of managerial flexibility and underestimated investment value. Real option analysis is studied as an effective approach to explore managerial flexibility and assess the value of uncertainty. A flexible guarantee-saving scheme model with the incorporation of Real option analysis is explored for the promotion of Energy performance contracting: (1) Option to expand is analyzed for Energy performance contracting participants; (2) Risk-profit allocation mechanism of guarantee-saving scheme model and its guarantee-value scope acceptable to participants are analyzed; (3) A minimum profit difference principle between participants (i.e., participants achieving their respective expectation) is proposed, and the primary optimization is performed; (4) Sobol-enabled global sensitivity analysis and deep optimization are implemented. A case study is used to demonstrate its effectiveness and applicability of the capability of the proposed model to optimize the guarantee value for the guarantee-saving scheme in Energy performance contracting. The results show that the scheme can be optimized to a balanced condition, where the investment value for both participants are maximized, and the profit difference between them can be reduced to $ 8.9. The results also present a better scheme scenario, an only $ 3.1 profit difference between participants and a higher total investment value, increased from $ 4,905,302 to $ 5,016,948.4, indicating that the project value of Energy performance contracting can be increased through deep optimization without harming the profit of any participant. The novelty of this research lies in (a) incorporating Real option analysis into Energy performance contracting to seek for the guarantee-value optimization, and (b) a deep guarantee optimization with parameter adjustment by global sensitivity analysis.